Collective properties of medium weight nuclei - Simpson, J (1966)
A study has been made of collective quadrupole phenomena in some medium weight nuclei. The nuclei studied are ones which are not understandable in terms of rotations of a symmetrically deformed nucleus. Two types of electric quadrupole phenomena have been determined, the electric quadrupole transition strength between the ground state and first excited state and the electric quadrupole moment of the first excited 2+ state in even nuclei. The method of Coulomb excitation, employing oxygen beams up to 45 MeV and sulphur beams up to 55 MeV from a tandem Van de Graaff generator, has been used, and the Coulomb excitation cross-section has been determined in two ways. One method was the magnetic analysis of the scattered oxygen ions from the target with a consequent determination of the excitation probability directly from the number of inelastic ions detected; the other method was the measurement of the number of deexcitation gamma rays in coincidence with the heavy ions detected at backward angles near 180°. The electric quadrupole transition strengths have been determined in a few single-closed shell nuclei and some of their isotopic neighbours. The upward reduced transition strengths, B(E2), for the ground to first excited state transition, in units of e2b2 , are as follows : Ti50, O.024 ± 0.002; Cr52 , O.048 ± 0.002; Fe54 , 0.051 ± 0.002; Ce140, 0.27 ± 0.04; Ce142, 0.42 ± 0.01; Nd142, 0.42 ± 0.05; Fd143 ± 0.047 ± 0.013; Nd144, 0.44 ± 0.02; Nd146 ± 0.65 ± O.01; Nd148, 0.96 ± 0.02; Sm144, 0.25 ± 0.04; Sm148 ± 0.79 ± 0.02; Sm150, 1.34 ± 0.06. The errors quoted on the Ce, Nd and Sm nuclei are relative errors and a 10% error should be added in quadrature to than to get absolute errors. A comparison of the B(E2) values with a pairing plus quadrupole force theory shows that the theory is quite successful for the single-closed shell nuclei, but for nuclei with only a few particles outside the closed shell, the theory grossly overestimates the transition strengths. The electric quadrupole moment of the first 2+ state in Cd114, in Sm148 and in Sm150 has been deduced using the reorientation effect of Coulomb excitation. The excited state quadrupole moment determined is for Cd114, -0.39 ± 0.24 b; for Sm148 , -0.78 ± 0.38 b and for Sm150 , -1.26 ± 0.23 b. These values are all substantially larger than the quadrupole moment due to a single proton thus emphasizing the collective nature of the low-lying states. The moments for Sm148 and Sm150 are of the magnitude expected for a fully deformed nucleus and the sign would imply a prolate shape, but these nuclei do not display rotational energy spectra. The nucleus Cd114 which displays one of the best harmonic spectra known would be expected to have no quadrupole moment. Thus the experimental quadrupole moments pose a serious problem about the mature of the lowest states in medium weight nuclei.